Digital Encounters of Surrogacy: Nodes of a Fictional Ethnography. (April 2022) - Daskalaki, Ivi; Apostolidou, Anna
The article addresses the question of alternative ways to writing ethnography and more specifically, the ethnography of surrogacy. It focuses on the example of a digital ethnographic artifact that was created in order to host fictional representations of surrogacy practices. The article presents ethnographic material from a recent research project that focused on experiences of surrogate parenthood of Greek and Cypriot intended parents. The digital artifact demonstrates how multimodal anthropological narrations may represent, and simultaneously evoke, sensory experience through the temporal and spatial digital unfolding of interlocutors' stories. Indeed, the article explains the structure of the artifact and discusses specific digital nodes which depict interlocutors' testimonies of longing, waiting, uncertainty, vulnerability, pain, loss, joy, and safekeeping before, during, and after surrogacy procedures. In the context of the ethnographic artifact narratives and non-narratives of motherhood, fatherhood, and pregnancy refer to a variety of precarious contexts of placeness/emplacement, legality/illegality, and connectedness/disconnectedness without relying on conventional textual ethnographic writing. Drawing from selected ethnographic examples as they relate to the literature of assisted reproduction, the authors argue that digital nodal narration enables both the cultural contextualization of individual experience as well as its affective and intellectual correlation with similar and antithetical experiences of other field interlocutors.